Prospective observational study of baloxavir marboxil in adults and adolescents with uncomplicated influenza from China - Liao, Guichan; Xia, Muye; Jiang, Yuanhui; Chen, Hongjie; Liao, Wei; Peng, Jie; Cai, Shaohang (Frontiers in Microbiology, 2023)
Introduction There are limited data on the efficacy of baloxavir marboxil (baloxavir) versus oseltamivir in Chinese patients with influenza A. Methods This study is an observational real-world investigation encompassing 246 patients (baloxavir, n = 147; oseltamivir, n = 99) confirmed positive for influenza A. The choice between baloxavir and oseltamivir antiviral treatments was determined collaboratively by the clinician and the patient. A thorough comparative analysis was undertaken between the two groups, examining parameters such as the duration of fever and symptoms, viral load dynamics, lymphocyte changes, and enhancements in health-related quality of life (QoL). Results No significant differences were observed in demographic data between the two groups. The duration of fever was significantly shorter in the baloxavir group (P < 0.001). However, the duration of symptoms was not significant different (P = 0.167). Multivariable Cox analysis showed the independent factors affecting duration of fever were baloxavir treatment (HR = 2.033, P < 0.001), fever on day 1 (HR = 0.741, P = 0.010) and CRP level (HR = 1.009, P = 0.039). Moreover, sex (HR= 0.660, P = 0.019) and monocyte count (HR = 1.355, P = 0.018) were independent factors affecting the duration of symptoms. No significant difference in change of health-related quality of life (P > 0.05), positive rate of viral antigen on day 3 (P = 0.477) between the two groups. Remarkably, a mutation was observed in one case on the third-day after baloxavir treatment compared with first-day, from cysteine to serine at position 384 of the PA subunit. Conclusion In the clinical setting, baloxavir demonstrated comparable clinical benefits to oseltamivir, establishing its efficacy as an effective antiviral therapy for Chinese patients with influenza.